VARIAN LINGUISTIK DIALEK YAMAGATA DAN DISTINKSINYA DARI BAHASA JEPANG BAKU - Diafi, Rafi’ Putra; Aibonotika, Arza; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was conducted to understand the Yamagata dialect and its differences within the standard Japanese language. The research employed a qualitative and descriptive method. The data source was derived from the Hougen Manual posters published by the Yamagata Prefecture Elderly Welfare Facility Council, General Incorporated Association. Data collection methods included observation, listening, and note-taking. The research findings revealed 19 pieces of data within the Yamagata dialect, indicating that the dialect exhibits several lexical differences, particularly in the use of verbs, when compared to other dialects in the Tohoku region. The results demonstrated that verb variations became a distinctive feature that sets the Yamagata dialect apart from other dialects. Nevertheless, the Yamagata dialect also displayed some similarities with the standard Japanese language, especially in terms of gokan (vocabulary) and gobi (particles), which could be found in specific words.Key words: Dialect, Yamagata, Morphology, Lexical, Hougen Manual